Testing game-based performance in team-handball - Wagner, H.; Orwat, M.; Hinz, M.; Pfusterschmied, J.; Bacharach, D. W.; von Duvillard, S. P.; Müller, E. (The Journal of Strength and Conditioning Research, 2016)
Team-handball is a fast paced game of defensive and offensive action that includes specific movements of jumping, passing, throwing, checking, and screening. To date and to the best of our knowledge, a game-based performance test (GBPT) for team-handball does not exist. Therefore, the aim of this study was to develop and validate such a test. Seventeen experienced team-handball players performed 2 GBPTs separated by 7 days between each test, an incremental treadmill running test, and a team-handball test game (TG) (2 × 20 minutes). Peak oxygen uptake (VO2peak), blood lactate concentration (BLC), heart rate (HR), sprinting time, time of offensive and defensive actions as well as running intensities, ball velocity, and jump height were measured in the game-based test. Reliability of the tests was calculated using an intraclass correlation coefficient (ICC). Additionally, we measured VO2peak in the incremental treadmill running test and BLC, HR, and running intensities in the team-handball TG to determine the validity of the GBPT. For the test-retest reliability, we found an ICC >0.70 for the peak BLC and HR, mean offense and defense time, as well as ball velocity that yielded an ICC >0.90 for the VO2peak in the GBPT. Percent walking and standing constituted 73% of total time. Moderate (18%) and high (9%) intensity running in the GBPT was similar to the team-handball TG. Our results indicated that the GBPT is a valid and reliable test to analyze team-handball performance (physiological and biomechanical variables) under conditions similar to competition.